The first twenty exercise training program and fire academy recruits’ fitness and health - Hollerbach, Brittany S. (Kansas State University, 2016)
Firefighting is an inherently dangerous occupation with high rates of injuries and fatalities, with the majority of line of duty fatalities due to cardiovascular events. Additionally, firefighters struggle with poor health and low levels of fitness, including very high (>80%) rates of overweight and obesity likely related to the culture of the fire service. Limited resources exist for fire departments that are sensitive to the culture and work requirements of these “tactical athletes”. Though there has been increasing interest in circuit-type high intensity exercise training programs, key research data are lacking for the firefighter population and few studies have focused on training firefighter recruits. PURPOSE: The purpose of this pilot investigation was to examine a novel physical training program on fire academy recruits’ health, fitness, and performance, in addition to examining the programs’ acceptability, feasibility, and future efficacy. METHODS: Thirteen participants were recruited from an entry level fire academy and were randomly assigned to either the control (CG, n=6) or intervention exercise group (TF20, n=7). Due to attrition within the first two weeks of the study, 10 male fire recruits (23±3 years) completed the study (CG, n=3, TF20, n=7). The CG were asked to continue their current exercise habits. TF20 were provided an online-based training program (The First 20) that included periodized workouts, nutritional information, and mental readiness education. All participants completed baseline and post-intervention assessments and 10-weeks of exercise training. Health assessments included resting and post-exercise heart rate and blood pressure and estimated VO₂[subscript]max. Anthropometric measures included height, weight, % body fat, % lean mass, and BMI. Performance was measured using the Candidate Physical Ability Test (CPAT). Psychosocial measures were assessed by a short questionnaire. A feasibility analysis was also completed for those in TF20 group. Due to the small sample size and group differences at baseline, descriptive statistics were calculated and each participant was reviewed as an individual case study. The Wilcoxon Signed Rank Test was used to test for significance among TF20 group. RESULTS: This pilot investigation provided effect sizes and parameter estimates necessary for the design of a larger randomized controlled trial. Even with a small sample size, TF20 group showed improvement on numerous outcome measures including CPAT performance (40% passing at baseline to 86% passing post-intervention). Of five TF20 participants completing the CPAT at baseline and post-intervention, four improved their passing time. TF20 participants significantly increased estimated VO₂[subscript]max (p=0.028) and significantly improved body composition (decreased fat mass (kg) and % fat mass, p=0.028). TF20 participants also significantly improved grip strength (p=0.018). The CG saw no statistically significant differences from baseline to post-intervention. TF20 group completed approximately 75% of the assigned workouts. Participants reported enjoying the workouts and stated a program like this should be offered for fire academy recruits in the future. CONCLUSION: While TF20 participants showed significant fitness gains, the small sample size limited comparisons to the control group or other covariates. TF20 program was well-received although there may be a better way to implement the intervention to increase participation. Participants mentioned they would like group workouts led by a certified strength and conditioning coach/peer fitness trainer as opposed to self-guided workouts. This investigation provides promising results for the efficacy of high-intensity training programs in firefighter recruits. Additionally, this study provides alternative guidance for exercise prescription designed specifically for the firefighter population.
Keywords: Firefighters; Occupational safety; Obesity; Exercise training